Electronic structures of luminescence centers in pure and defective scintillation crystals AWO4 (A = Pb, Cd, Zn) - Hizhnyi, Iu. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The electronic structures of the set of molecular clusters of dielectric oxide crystals AWO4 (A = Pb, Cd, Zn), the sizes of which increase sequentially are ab-initio calculated by the Restricted Hartree-Fock (RHF) method. The results of calculations of molecular orbitals and energy dependences of partial densities of electronic states of different clusters are compared each to other and to experimental data. It is found that calculated electronic structures of the tungstate groups and cations which are surrounded in cluster by certain number of the nearest neighbor atoms of the crystals quite well represent the experimentally obtained value of the forbidden gap of corresponding AWO4 crystal.